Protective and Vulnerability Factors in Self-Esteem: The Role of Metacognitions, Brooding, and Resilience - Hagen, Roger; Havnen, Audun; Hjemdal, Odin; Kennair, Leif Edward Ottesen; Ryum, Truls; Solem, Stian (Frontiers in Psychology, 2020)
The aim of the current study was to explore protective (resilience) and vulnerability factors (dysfunctional metacognitions and brooding) for self-esteem. A total of 725 participants were included in a cross-sectional study. A path analysis revealed five paths to self-esteem. The three main paths were: 1) symptoms -> metacognitions -> brooding -> self-esteem, 2) symptoms -> resilience -> self-esteeem, and 3) a direct path from symptoms. The first path corresponds with the metacognitive model of psychopathology and suggests that triggers in the form of anxiety and depression symptoms lead to the activation of metacognitive beliefs, which in turn activates brooding in response to these triggers. When a person engages in brooding this makes the person vulnerable to experiencing low self-esteem. The second path suggests a protective role of resilience factors. The overall model explained 55% of the variance in self-esteem. Regression analysis found that unique predictors of self-esteem were female sex, symptoms of anxiety and depression, brooding, and resilience. These findings have possible clinical implications, as treatment may benefit from addressing both protective- and vulnerability factors in individuals suffering from low self-esteem.